Actualization of Religious Figures in Building a Culture of Peace in Plajan Pakis Aji Jepara - Muhammad Misbahul Huda (LPPM Institut Pesantren KH. Abdul Chalim, 2021)
The lack of understanding of the culture of peace and the inadequate actualization of religious leaders (Islam, Christianity, and Hinduism) in Plajan Village, has resulted in the stagnation of a culture of peace that has been formed for a long time. Therefore, it is necessary to optimally actualize religious figures (Islam, Christianity, and Hinduism) in Plajan Village. This is because religious leaders are the key agents in fostering religious communities and as projections of the examples of religious adherents. To be stronger, it can also be added with innovation in the realm of peace management. Peace management is the answer to various challenges of division, conflict, and so on. Because peace management emphasizes intensive dialogue or interaction between religious leaders and religious communities. This research methodology uses qualitative research with a case study approach. Data collection techniques through observation and documentation methods. While the data analysis technique uses the Miles Huberman model, which consists of three stages, namely data reduction, data presentation, and drawing conclusions.